Budaya Politik Transaksional dan Tantangan Partisipasi Publik Dalam Demokrasi Indonesia Era Digital - Rahsya Auliya; Rifki Al Ahsa; Royan Zulkarnaen; Wasis Amad Dhani; Rudi Santoso (JURNAL ILMIAH NUSANTARA, 2026)
Abstract. This article examines the persistence of transactional political culture and its implications for public participation in Indonesia’s digital-era democracy. The background of this study lies in the increasing integration of digital technology into political processes, which on one hand expands access to participation, but on the other hand creates new spaces for pragmatic and transactional practices. The objective of this research is to explore how transactional politics adapts within digital environments and how it influences the quality of civic engagement. This study employs a qualitative approach through literature review and descriptive analysis, focusing on recent political phenomena, digital campaigns, and patterns of voter behavior. The findings indicate that transactional politics has not diminished; instead, it has transformed into more subtle and technologically mediated forms, such as digital campaigning incentives, micro-targeted messaging, and online influence operations. While digital platforms potentially encourage broader participation, they also risk reinforcing superficial engagement driven by short-term incentives rather than substantive political awareness. The study also highlights structural challenges, including digital inequality, low political literacy, and the dominance of elite-controlled narratives. The implications suggest that strengthening democratic participation requires not only technological access but also critical awareness, ethical political communication, and institutional commitment to transparency. Without these, digital democracy may reproduce existing inequalities rather than resolve them.